An empirical mediation analysis of technological innovation based on artificial intelligence in the relationship between economic development and corporate governance mechanism - Khan, Muhammad Anees; Mazliham, M. S.; Alam, Muhammad Mansoor; Aman, Nida; Malik, Sakshi; Urooj, Syeda Faiza; Taj, Tanveer (Frontiers in Environmental Science, 2022)
Although strong recommendations and steps have been developed and taken to adopt the latest technological trend through corporate governance reforms for improving the economic development, however, the trend toward adopting the latest technology has not been adopted and thus has remained a big issue in the non-financial sector for the last two decades around the globe. The study used GLS (random effect) regression estimator to a sample composed of 1600 firm-year observations from 2017 to 2021. The findings indicated that the majority of the firms were involved in an income-decreasing economic situation. Moreover, the findings evidenced that compliance with some specific CG attributes welcomed the technological innovation and significantly had an impact on the economic development. However, some CG attributes of the models did not play any significant role in technological innovation and economic development which needs improvement. Moreover, this study also evidenced that the impact of CG attributes is not directly affecting economic development but is mediated by the technological innovation, which is of importance to managers of a firm, who hold responsibility for investing and financing activities. In addition, this study revealed a fully significant mediating role of technological innovation in the relationship of BOD meetings, audit committee size, managerial ownership, and foreign ownership with economic development. However, no significant mediating role of technological innovation was observed in the relationship of independent BOD and economic development. All in all, the results of this study have significance for regulatory bodies, researchers, academic researchers, practitioners, publicly listed companies in Malaysia, the Bursa Malaysia and the security commission to uplift their financial performance and curb EM activities through the effective use of CG mechanisms.